2006
DOI: 10.1051/0004-6361:20053219
|View full text |Cite
|
Sign up to set email alerts
|

An abundance analysis of the symbiotic star CH Cygni

Abstract: The photospheric abundances for the cool component of the symbiotic star were calculated for the first time using high-resolution near-infrared spectra and the method of of standard LTE analysis and atmospheric models. The iron abundance for CH Cyg was found to be solar, [Fe/H] = 0.0 ± 0.19. The atmospheric parameters (T eff = 3100 K, log g = 0.0 (cgs), ξ t = 2.2 km s

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 32 publications
(48 reference statements)
1
40
0
Order By: Relevance
“…In Fig. 9 the position of our giants with highest 12 C/ 13 C ratio is less elevated in log N-log C plane similar to CH Cyg for which Schmidt et al (2006) obtained 12 C/ 13 C = 18. In Fig.…”
Section: Discussionsupporting
confidence: 63%
“…In Fig. 9 the position of our giants with highest 12 C/ 13 C ratio is less elevated in log N-log C plane similar to CH Cyg for which Schmidt et al (2006) obtained 12 C/ 13 C = 18. In Fig.…”
Section: Discussionsupporting
confidence: 63%
“…With a distance of 245 ± 40 pc (from the Hipparcos parallax; Perryman et al 1997), it is one of the nearest symbiotic stars. Of the two known photometric periods, the 756 day period is thought to be due to pulsation of the M giant (Schmidt et al 2006), and the 14.5 year period is probably the orbital period. CH Cyg was detected in the BAT survey.…”
Section: Symbiotic Star Identifications and Bat Resultsmentioning
confidence: 99%
“…Since 1964, CH Cyg has displayed a number of outbursts. Schmidt et al (2006) showed both the photospheric features of the cool giant and the nebular emission lines in CH Cyg. The average C/N and O/N ratios of the cool giants in CH Cyg are respectively 1.6 and 4.0, which are typical abundance ratios of M giants.…”
Section: Chemical Abundance Of Symbiotic Nebulaementioning
confidence: 96%